Microornamentation on snake scales - Singh, Ishan (My University, 2018)
The morphology and functionality of surface microornamentation in southern African snakes is well-established in terms of resulting optical effects. Velvet-blackness, a type of optical effect is produced when light incident on a scale is scattered by microornamentation. I tested microornamentation from Bitis arietans dorsal exuvia for these optical effects. Scales were excised from shed skins of B. arietans and sputter coated with 15 nm Gold-Palladium to control the effect of pigment. Spectral intensity (SI) of three scale regions of known micro topography was recorded using spectrophotometry over the visible spectrum only as a measure of reflectivity of the scales. Given that surface roughness (the deviation of a membrane’s surface topography from an ideal surface) is a product of the size of surface asperities and its degree of randomness, the three scale regions in order of decreasing surface roughness were dark (dorsal) scales, pale (dorsal) scales, and ventral scales. Measures of SI on dorsal and ventral scale regions revealed lowest SI on dark dorsal scales and highest on ventral scales. In general, the level of micro-structuring was inversely proportional to SI. To test if optical effects are angle-dependent, I measured differences in SI between normal (90) and oblique (45) angles of incidence. Differences in SI between 90 and 45 were significant for all scale regions which revealed that while microornamentation produces optical effects at both normal and oblique incidence, the effect is greater at 45. Given that SI varies with surface roughness such that dark scales have a lower SI than pale scales, I conclude that scale colour in B. arietans is a product of optical effects created by microornamentation. The optical effect may improve the visual camouflage of B. arietans during ambush. While microornamentation is best known for its optical effects, it may have other functions. I examined the microornamentation in Bitis schneideri (Namaqua Dwarf Adder) using electron microscopy and found small, tooth-like protuberances distributed uniformly across the scales and across all body regions. I measured the distance between adjacent denticles which I 5 compared to the mean dimensions of sand grains from two study sites: Noup, within the distribution of B. schneideri, and Tswalu, outside of it but with significantly smaller grains. The space between denticles is smaller than sand grains from both sites. Due to its physical characteristics, microornamentation in B. schneideri has the potential to restrict sand grains from direct contact with the scale surface. These results suggest that microornamentation can function to shield the integument from sand abrasion in B. schneideri. This study demonstrates specific functions of microornamentation in the ecology of two species of Bitis.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Science, Johannesburg 2018
Keywords: Snakes--Ecology; Reptiles--Ecology; Snakes--South Africa